Analisis Usability Pada Website Terhadap Tingkat Retensi Pelanggan Pada Jd.Id Berbasis ISO 9241-11 - Laras Miranti Sanyoto; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
JD.id is one of online retail shop which give the conveniences for its customers to purchasing their needs. JD.id still receive many complains about the website's usability such as information discrepancies on the website, inconsistence language usage, and difficulties in understanding information on the website. This research was conducted to determine the quality of JD.id website service towards customer retention based on ISO 9241-11, regarding the influences of Effectiveness, Efficiency, and Satisfaction variables individually or collectively. The data of this study gathered using questionnaires as research instrument. The questionnaire consist of 27 statements that took sample of 100 respondents. The results shows that Effectiveness, Efficiency, and Satisfaction variables individually or collectively have effects the customer retention, when the three variables are increasing it will influence the customer loyalty to use the site. Effectiveness, Efficiency, and Satisfaction variables collectively influenced about 44,6% to Customer Retention. The results of this study will give recommendations to the content, preparation and ease of reading information, links and navigations indicators.